Propuesta de un manual de funciones por competencias, valuación de puestos y un reglamento de admisión y empleo para el talento humano de la empresa Armiled Cia. Ltda. de la ciudad de Loja - Bustamante Córdova, Carlos Alberto (2016)
This research aims to improve the management of human talent in the company and contribute to the fulfillment of the functions of each position for personal, therefore set as its main objective to propose a Function Manual, valuation of positions and regulations admission and employment for the human talent of the company ARMILED CIA. LTDA. Loja City”. To meet the objective investigative methods were applied as: Deductive to gather information, Inductively for the analysis of the current situation of the company, the Descriptive detailing current and Analytical problems interpreting the data; using research techniques: direct observation, interviews the Regional Coordinator and all staff survey, these allowed to collect accurate and current development of human resources in the enterprise. Therefore this research project is a set of qualitative and quantitative data that allows for the final result the development of the Manual Job classification, Valuation of Posts and Regulation of Admission and Employment, these administrative tools will be useful for Business development and presenting key data on each workstation that integrates the Organization. After the project developed successful solutions could propose allowing ensure allocation of responsibilities to members of the organization and duplication of functions by the Post Classification Manual, which comprise 10 positions eliminated properly detailed. Valuation of Positions allows to demonstrate the proper wage to the functions performed. By developing de la investigation it was determined an assessment factor of 2.25 for the posts. Regulation of Admission and Employment developed according to the scheme and parameters defined by the Labour Code , in order to improve the induction selection of company personnel , supporting recruitment able to contribute to meeting organizational objectives business.